Forecasting: necesidades desde la educación contable para su abordaje (2016)
The forecast is an instrument made to predict the results of one or more operations from strategic areas which, when combined, can produce effects on the current and future financial statements. This possibility is linked to the fulfilment of the organization’s strategic objectives, as the analysis of these predicted effects can be confronted with the viability of the operations carried out or due to be developed.The design and implementation of tools such as forecasting require more than just the domain of control methods; they require creativity and resourcefulness when articulating the strategic processes within organizations. This topic unfolds itself within a decision-making framework under  uncertainty. Therefore, the requirements for accounting education in control areas become relevant from an interdisciplinary perspective.In this regard, within the subjects of management accounting, it is appropriate to address topics such as forecasting and the various techniques that are used to support the prediction processes within companies, which are mainly from statistics, econometrics, operations management and operations research.